A constructivist approach to learning an interactive multimedia course: Malaysian students' perspectives - Neo, Mai; Neo, Tse Kian; Tan, Gillian Xiao Lian (ASCILITE, 2007)
We present an alternative method in the constructive perspective to enhance student learning through a multimedia project, in which computing and multimedia technologies are used to enable students to participate more actively in their own learning. Students in a second year course in the Multimedia University, Malaysia, used the multimedia development process (MDP) to build a project in a collaborative, problem solving learning environment. They worked in groups and sought to solve their design problems as a team, with the teacher acting as a facilitator supporting them in their learning. Results showed that this method enhanced learning and improved understanding of the subject.